Are Tribal Adolescents Mentally Healthy? An Introspect with a Community Based Cross Sectional Survey in a District of West Bengal - Gandhari Basu; Sakrajit Maity; Anupam Ghosh; Suman Kumar Roy (Medsci Publications, 2018)
Background: Literatures reported psychosocial and behavioural problems among adolescents in different parts of India but research among tribes was quite less in spite of marginalised section. The study was conducted to screen for the prevalence of psychosocial symptoms and strengths and to find out factors with increased score among the tribal adolescents of a district of West Bengal. Methods: This community based cross sectional, descriptive study was done among 190 tribal adolescents with a pre designed, semi structured proforma including strength and difficulties questionnaire (SDQ). Anthropometric measurements were recorded. Census was done for selection of participants. Main findings: Out of 190 adolescents, 60.0% were male and six females were married. The illiteracy rate was two times in mothers. Proportion of overweight was significantly more in older adolescents (p<.05). Two thirds (66.8%) were at substantial risk of development of clinically significant mental health problems. Peer problems were most prevalent one. 26.8% had definite and 7.9% had severe difficulty problems. Parenteral fight had upset 92.6% adolescents and nearly half were unable to cope with their study. Economic difficulty, living in a happy family, inability to cope up with study and tension by parents expectation had significant association with increased total difficulty score (p <.05). Conclusions: This study revealed high prevalence of mental problems and distress by multiple events.